Use of Head Circumference as a Predictor of Height of Individual - Mansur, DI; Haque, MK; Sharma, K; Mehta, DK; Shakya, R (Kathmandu University Medical Journal, 2015)
Background Establishing personal identity is one of the main concerns in forensic investigations. In forensic anthropology, estimation of height from head circumference has a significant role in establishing personal identity. Objective The objective of the present study was an attempt to understand the relationship between height and head circumference of an individual and to derive regression formulae to estimate the height from the head circumference. Method The present study consisted of 440 (258 male and 182 female) students of age group 17 to 25 years studying in Kathmandu University School of Medical Sciences, Dhulikhel, Nepal during the period from November 2012 to October 2013. Height and head circumference of an individual were measured in centimeter. Data were analyzed by using statistical software SPSS-16 Result The findings of the present study were significant correlation between height and head circumference (r = 0.443, p < 0.01 for male, r = 0.302, p<0.01 for female, and r = 0. 398, p < 0.01 for combined (male and female). The regression equation for height and head circumference was found to be Y = 1.734X + 70.36 (R2 = 0.196) for male, Y = 0.916X + 106.8 (R2 = 0.091) for female, and Y = 1.648 X + 71.69 (R2 = 0.158) for combined (male and female), where Y is the height of Individual and X is the Head Circumference. Conclusion Head circumference showed highly significant positive correlation with individual’s height. Therefore, the present study will help in medico-legal cases in establishing the identity of an individual and this would also be useful for Anatomists and Anthropologists. Kathmandu University Medical Journal Vol.12(2) 2014: 89-92